Low-molecular-weight heparin-induced thrombocytopenia with multisite embolism: successful management with argatroban and dabigatran – a case report and literature review - Zhao, Huixin; Tang, Xiaowan; Song, Xitao (Frontiers in Pharmacology, 2025)
Heparin-induced thrombocytopenia (HIT) is a rare but potentially life-threatening complication, with an incidence ranging from approximately 0.2%–5.0%. The risk of HIT associated with low-molecular-weight heparin (LMWH) is nearly ten times lower than that of unfractionated heparin (UFH). However, LMWH can still induce severe thrombocytopenia and thromboembolic events. This study presents a rare case of LMWH-induced severe type II thrombocytopenia complicated by multiple thromboembolic events. An elderly patient developed HIT following LMWH administration and experienced worsening embolic symptoms after platelet transfusion. The patient received timely discontinuation of heparin analogues and initiation of argatroban therapy with close monitoring of activated partial thromboplastin time (APTT). This was followed by a transition to dabigatran etexilate, which successfully prevented life-threatening embolic complications, limb amputation, and mortality. This case underscores the importance of maintaining a high level of clinical vigilance despite the rarity of LMWH-induced HIT. Once HIT is diagnosed, all forms of heparin should be discontinued immediately, and the decision to administer platelet transfusion should be made with caution to prevent exacerbation of thrombosis. This study provides valuable insights into the early recognition and optimal management of LMWH-induced HIT.